(untitled) (Pedagogical Horizons, 2025)
This article examines how democracy education can be implemented in everyday school life through theatre education methods, especially improvisation. Building on the concept of ‘democracy as a way of life’ (Himmelmann, 2004) and the teaching principle of political education, approaches to democracy education and theatre education are brought together. A teaching example illustrates how improvisational methods can promote democratic learning processes; practical tips provide teachers with ideas for their own use.